The Existing Information System At All Levels of Health Service Facilities in Depok City, 2017 - Siregar, K N; ., Besral; Kurniawan, R; Affriansyah, E; Sutiawan, R; Maulina, F C; Nuridzin, D Z (KnE Life Sciences, 2018)
One of the advantages of electronic information system is data sharing. Data sharing would be beneficial for the patients when there is system integration among health service facilities. One of the constraints is there is no standardized system yet, so that every health service facility develops its own system according to its needs and the capacity of the stakeholders. This study is one stage of system-development life cycle, which focuses on system description to assess the gaps between the existing system and the standard. This study was conducted in health service facilities that have potentials to be part of referral network with University of Indonesia Hospital. The health service facilities consist of three major groups: Primary Healthcare (Puskesmas), Private Clinic and Hospital, and General Hospital of Depok. The assessment focuses on three major aspects: Technical including infrastructure and technology, staff behaviour, and organization. The Electronic Medical Record (EMR) is not well functioning yet, and currently the running electronic system is for the billing. Recording, compilation, storage, analysis, and reporting data apparently are better functioning in private clinic and hospital as they have clear SOP and punishment mechanism. Data sharing is generally still limited to manually written medical resume, and there are no formal data sharing at all health service facilities. Conclusion. Not all health service facilities have are using standardized EMR, so that they are not capable of conducting data sharing among health service facilities under wider Electronic Health Record (EHR) mechanism. Keywords: EMR (Electronic Medical Record), EHR (Electronic Health Record), data sharing